Gas sorption and diffusion damages by guar-based fracturing fluid for CBM reservoirs. (1st September 2019) - Huang, Qiming; Liu, Shimin; Wang, Gang; Wu, Bing; Yang, Yun; Liu, Yu
Abstract: The fracturing fluid is commonly used in the CBM reservoir. Long-term field applications show that the fracturing fluids can have adverse impacts on gas transport and flow capacity for CBM reservoirs. In this study, we investigate the effect of guar-based fracturing fluid on gas sorption capacity and diffusion under different fracturing fluid treatment conditions. The Illinois coal samples were initially treated by guar-based fracturing fluid followed by isotherm sorption and diffusion experiments. We also conducted microscopic observation and 13 C nuclear magnetic resonance to characterize the guar-coating effect and geochemical evolution of coal microstructures. Our experimental results show that the residue of the guar-based fracturing fluid can result in damages of gas sorption and diffusion because of the guar-coating. The degree of damages does not correlate with concentration of hydroxypropyl guar (HPG). The Langmuir pressure of the guar gel treated coal samples were significantly reduced which hinders gas desorption during the well depletion. The gas diffusivity in the macropore of the coal matrix was damaged significantly after the guar gel treatment. It was also observed that the water washing can effectively recover the gas sorption capacity and diffusivity which implies that the flowback can remove the residual guar during the flow back period after the stimulation. Based on the microscopic observation and NMR results, it was found that the HPG can coat on the coal particles and hinder the gas sorption and diffusion, but no obvious functional group change on the coal surface with the treatment. The findings of this work can provide valuable data for the guar-gel fracturing stimulation optimization for CBM reservoirs.